Learning Environment Related Factors Affecting Afghan EFL Undergraduates’ Speaking Skill - Hazrat Usman Mashwani; Siti Maftuhah Damio (Universitas Muhammadiyah Yogyakarta, 2022)
Of the four language skills, speaking is usually considered an indicator of proficiency in a language. As an EFL student, one should master speaking skill (Nazara, 2012). Unfortunately, most Afghan EFL undergraduates are not as good at speaking as they are in the other three English language skills (reading, writing and listening). Most Afghan undergraduate EFL learners are good at reading and writing, but in part of oral communication, they are not accurate and fluent (Zia Sulan, 2015). Hence, this study was conducted to investigate the factors that affect the Afghan undergraduate EFL learners’ speaking skill at Sayed Jamaluddin Afghani University Kunar, Afghanistan. The study specifically investigated the learning environment-related factors that affected student speaking skill. A mixed method was used for this study, i.e., quantitative (questionnaire) and qualitative (interview). The questionnaire data were descriptively analyzed in SPSS version 20 and presented in figures and tables. The interview data were thematically analyzed and presented. A total of 90 students (40 junior and 50 senior) were purposively selected and participated in this study. The findings revealed that large classes and the lack of basic facilities in the speaking classroom were some factors in the learning environment that affected the students speaking skill. The current study’s findings will hopefully help teachers and educators be attentive and creative in building a proper learning environment to reduce the factors that affect students’ speaking skill.